Neutron Permeation Properties and Characterization of Synthesized Non-Hydrated Magnesium Borate Minerals - Seyhun Kipcak, Azmi; Moroydor Derun, Emek; Tugce Senberber, Fatma; Dere Ozdemir, Ozgul; Yilmaz Baysoy, Derya; Piskin, Sabriye (Asian Journal of Chemistry, 2014)
Magnesium borates are excellent materials due to their thermal and mechanical properties. In this study, the thermal (solid-state) synthesis was used for the production of non-hydrated magnesium borate minerals. In the X-ray diffraction results of thermal synthesis, Kotoite (K) "01-075-1807, Mg3(BO3)2", Suanite (S) "01-086-0531, Mg2(B2O5)" and (MgB1) "00-031-0787, MgB4O7" and (MgB2) "01-073-2232, Mg2B2O5" were produced. Higher XRD scores were seen at the molar ratios of 3:2 and 1:1. Materials, XRD scores increased with increasing temperature and time. Molar ratios, reaction temperature and time for the best crystal magnesium borate materials production were determined as 3:2-1:1, 1000 °C and 240 min. Products at the highest XRD scores were subjected to neutron permeability analyses. Neutron permeability decreased with increasing thickness of the material. Increase of molar ratio of the raw materials contributed to the neutron permeability of product. The lowest values of total macroscopic cross section and neutron permeability have been found for 3:2 of MgO:H3BO3 ratio and 1.25 cm thickness.